2004
DOI: 10.1021/bi035874n
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Second Step of the Trans Excision-Splicing Reaction of a Group I Ribozyme by Exploiting P9.0 and P10 for Intermolecular Recognition

Abstract: We previously reported that a group I intron-derived ribozyme can catalyze the excision of targeted sequences from within RNAs in vitro and that dissociation of the bridge-3' exon intermediate between the two reaction steps is a significant contributing factor to low product yields. We now analyze the effects of increasing the length, and thus the strength, of helices P9.0 and P10, which occur between the ribozyme and the bridge-3' exon region of the substrate, on this trans excision-splicing reaction. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…3B) may be the faster transsplicing kinetics with short substrates. Several processes may play a stronger role at faster reaction kinetics, such as the initial folding of the ribozyme (Pan et al 1997;Shi et al 2009) and later steps in the trans-splicing process (Karbstein et al 2002;Bell et al 2004), which are not captured by the thermodynamic model used in this study.…”
Section: Calculation Of Dg Bind For Trans-splicing Ribozymesmentioning
confidence: 99%
“…3B) may be the faster transsplicing kinetics with short substrates. Several processes may play a stronger role at faster reaction kinetics, such as the initial folding of the ribozyme (Pan et al 1997;Shi et al 2009) and later steps in the trans-splicing process (Karbstein et al 2002;Bell et al 2004), which are not captured by the thermodynamic model used in this study.…”
Section: Calculation Of Dg Bind For Trans-splicing Ribozymesmentioning
confidence: 99%
“…The design of the in vivo TES test system was based on work involving the trans-splicing ribozyme (Sullenger and Cech 1994;Jones et al 1996;Jones and Sullenger 1997;Phylactou et al 1998;Kohler et al 1999;Rogers et al 2002;Byun et al 2003;Ryu et al 2003;Kastanos et al 2004;Shin et al 2004), as well as design principles garnered through studies of the TES ribozyme in vitro (Bell et al 2002(Bell et al , 2004. Our simplest TES reaction system involves the removal of a single nucleotide from a substrate, so we designed a test system in which we create a single base insertion mutation in the coding region of GFP ( Fig.…”
Section: Design Of the In Vivo Test Systemmentioning
confidence: 99%
“…In all the test systems, the length of recognition element 1 (RE1) was maintained at six bases. Previous work on the TES ribozyme indicated that increasing the length of RE3 can be beneficial to the reaction (Bell et al 2004), while work with the trans-splicing ribozyme showed a requirement for increased 3 0 exon interactions for in vivo activity (Kohler et al 1999;Rogers et al 2002;Byun et al 2003;Ryu et al 2003;Kastanos et al 2004;Shin et al 2004). Thus, ribozymes were tested with RE3 lengths of three bases (native length), five bases, and seven bases.…”
Section: Design Of the In Vivo Test Systemmentioning
confidence: 99%
See 2 more Smart Citations